Relationship Between Seasonal Oceanographic Parameter Fluctuations And Migration Of Mackerel Fish In Bengkulu Waters 2013-2023 - Nasya, Angel Pauline; Norfahmi, Siti Hairunnisa; Supiyati; Erwina, Yuyun (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
Mackerel fish are a high-value fishery commodity whose migration patterns are influenced by several oceanographic factors. This study aimed to identify the influence of seasonal fluctuations in oceanographic parameters on the migration of tenggiri fish during 2013-2023 in seven waters of Bengkulu. Oceanographic data were obtained from the Marine Copernicus. The data were obtained from the Multi-Observation Global Ocean 3D Temperature Salinity Height Geostrophic Current and MLD product for the period from 2013 to 2023, with a spatial resolution of 0.125°, while the catch data were obtained from the Bengkulu Province Marine and Fisheries Department. The data were processed spatially and temporally using GrADS, Panoply, and ArcGIS. The results of the study show that temperature, salinity, and currents tend to be stable throughout the year, whereas chlorophyll-a and wind experience significant seasonal fluctuations. In Kaur, Bengkulu City, and North Bengkulu regions, spikes in chlorophyll-a and wind intensity during the Australian Monsoon and Transition II were positively correlated with increased mackerel catch yields. Conversely, areas such as Seluma and Central Bengkulu did not show a clear relationship between oceanographic parameters and catch yield. These findings confirm that chlorophyll-a and wind play a greater role in mackerel migration than do temperature or salinity.